Pengaruh Brand Association, Brand Loyalty, dan Kualitas Produk terhadap Keputusan Pembelian di Zangrandi Surabaya - Phoa Jocelyn Azelia Pandy; Michael Ricky Sondak (Fakultas Pariwisata Universitas Pancasila, 2015)
This study used a quantitative research that aims to determine whether the brand association, brand loyalty, and product quality influence on purchase decisions in Zangrandi Surabaya. Variables used in this research were brand association as the first independent variable (X1), brand loyalty as the second independent variable (X2), and product quality as the third independent variable (X3). Dependent variable in this study was the purchase decision (Y). There were 100 respondents selected as a sample using purposive sampling method. Data was collected by using questionnaire spreaded to the customer who consumed at Zangrandi Yos Sudarso. The data was analyzed using multiple linear regression analysis techniques then processed using SPSS 21 software. Based on the data analysis, it can be concluded that brand association variable, brand loyalty variable and the quality of the products variable had partial effect on purchasing decisions, as well as brand association variable, brand loyalty, and product quality collectively influence simultaneously on purchasing decisions.